Upaya Perbankan Syari’ah Dalam Perkuatan Permodalan Sektor Riil - Inne Risnaningsih; Heni Mulyasari (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2021)
It is not surprising that a number of leading economists criticize and worry about the economic capacity of capitalism in realizing economic prosperity on this earth. In the capitalist (conventional) economic theory, a new monetary approach, whether consciously or not, is the point of view of Islamic economics in the monetary sector, such as the role of money, interest, and bank credit. Meanwhile, negative values, destructive concept and theory paradigms, materialism philosophy, moral neglect and many more concepts of capitalism in the monetary and economic development fields must be deconstructed. Now it is up to the academics and practitioners of sharia economics to present a sharia economic construction that is truly fair, maslahat, and can realize the welfare of mankind without financial crises, economic stability without oppression, injustice and exploitation, both between individuals and companies, the state against the company and the rich country against the poor country.